Exopolysaccharide II Is Relevant for the Survival of Sinorhizobium meliloti under Water Deficiency and Salinity Stress - Primo, Emiliano David (2020)
Sinorhizobium meliloti is a soil bacterium of great agricultural importance because of its ability to fix atmospheric nitrogen in symbiotic association with alfalfa (Medicago sativa) roots. We looked into the involvement of exopolysaccharides (EPS) in its survival when exposed to different environmental stressors, as well as in bacteria-bacteria and bacteria-substrate interactions. The strains used were wild-type Rm8530 and two strains that are defective in the biosynthesis of EPS II: wild-type Rm1021, which has a non-functional expR locus, and mutant Rm8530 expA. Under stress by water deficiency, Rm8530 remained viable and increased in number, whereas Rm1021 and Rm8530 expA did not. These differences could be due to Rm8530's ability to produce EPS II. Survival experiments under saline stress showed that viability was reduced for Rm1021 but not for Rm8530 or Rm8530 expA, which suggests the existence of some regulating mechanism dependent on a functional expR that is absent in Rm1021. The results of salinity-induced stress assays regarding biofilm-forming capacity (BFC) and autoaggregation indicated the protective role of EPS II. As a whole, our observations demonstrate that EPS play major roles in rhizobacterial survival.